A taxonomic study of Praxelinae (Asteraceae—Eupatorieae) in Rio Grande do Sul, Brazil - Christ, Anderson Luiz; Ritter, Mara Rejane (Phytotaxa, 2019)
The Praxelinae comprises two genera—Praxelis and Chromolaena—and 19 species in Rio Grande do Sul, the southernmost State of Brazil. This is the first taxonomic treatment of these genera in the state according to their current circumscriptions. Chromolaena squarrosoramosa is formally reported for the first time for the flora of the state. The names C. callilepis and C. paraguariensis are used for the first time to refer to species previously known as Eupatorium polyanthum and E. angusticeps. Eupatorium angusticeps, considered in previous studies endemic to Rio Grande do Sul and probably extinct, is synonymized under C. paraguariensis and has its geographical range extended. Two neglected names, C. elliptica and C. latisquamulosa, are re-established, and C. umbelliformis is synonymized under C. elliptica. Furthermore, C. rhinanthacea is recollected for the first time after 40 years, and C. gentianoides is rediscovered in the state after almost 200 years of the original collection. Identification key and morphological descriptions, as well as distribution maps, field photographs, illustrations and general comments on the biology, ecology and identification of the species are provided.